Recent advances in surface‐functionalised photosensitive antibacterials with synergistic effects. Issue 4 (4th December 2019) - Liao, Peizi; Hu, Jiahao; Wang, Huagao; Li, Jinyang; Zhou, Zuowan
Abstract : The alarm has been ringing over the gradually increasing drug‐resistant bacteria, which calls for the development of safer antibacterial materials. Photosensitive antibacterials are considered as a promising alternative solution due to their unique light‐activated antimicrobial mechanism, which in‐situ produces highly reactive oxygen species on the multiple and variable active sites for the inactivation of various microbes. However, there are some factors, including phototoxicity, oxygen consumption and the risk of microbial contamination, greatly limit the efficiency and application of photosensitisers (PSs) in practical biomedical applications. Some studies have explored the synergistic effects of PSs by antibiotics, photothermal agents, antibacterial nanoparticles and biofilm‐disrupting enzymes. Moreover, novel synergistic methods for improving the antibacterial ability of PSs under low‐energy irradiation, hypoxia conditions and dull conditions, have been rarely reviewed yet. Herein, the authors summarised some synergistic methods and related applications of surface‐functionalised photosensitive antimicrobials, which were prepared with organic antimicrobial materials, superhydrophobic surfaces, upconversion nanoparticles and energy storage structures in recent years. Finally, the authors presented the advantages and challenges of these synergistic mechanisms, and further analysed the development trend and application prospects of the surface‐functionalised photosensitive antibacterials in biomedical fields.